Impact of E-Education on Higher Education in India - G. Sreenivasa Reddy, Chandapuram Sri Likhitha, Regadda Padma Nandini (Mathematical Statistician and Engineering Applications, 2023)
Due to outbreak of corona virus around the country all the educational institutions have been closed with this reason many educational institutions have taken a bold step by continuing academics by using online platforms. The study was focused on impacted areas of higher education. During the study it is found that with the pandemic situation the education system has affected. To overcome some challenges some of the educational institutions was adopted the e-education. But, from the study it is clear that all the major areas of higher education are got impacted with e-education system. The study suggested during this pandemic, the HEIs shouldfocus more on virtual educational activities includingtelevision, and web-based education.